2019
DOI: 10.3390/nano9020213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity on Silica Nanoparticle Adsorption Kinetics and Mechanisms for Fluid/Rock Interaction with Calcite

Abstract: This study addresses the kinetics of silica nanoparticle adsorption on calcite from a solution at three salinities: deionized water (DIW), synthetic seawater (SSW), and low salinity water (LSW). The nanoparticle adsorption mechanisms and the effects on calcite dissolution are addressed. It was shown that nanoparticle adsorption was best described with the second-order-kinetic model and that silica nanoparticle adsorption reduced calcite dissolution. This was confirmed by measuring the Ca2+ ion concentration, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The surface charge measured in distilled water was negative for BSA-SeNPs (−34.5 mV), UD-SeNPs (−26.6 mV), and AgNPs (−29.8 mV) and positive for CS-SeNPs (+24.4 mV). Generally, the ions in PBS seemed to neutralize the zeta potential attributable to an increased salt concentration in PBS. , However, even using PBS instead of water to dissolve the NPs, BSA-SeNPs, UD-SeNPs, and AgNPs remained negatively charged, while CS-SeNPs stayed positively charged (Table ). Cao et al (2019) reported that the positive surface charge provided by CS could be mainly attributed to NH 3 + groups, while the net negative charge in BSA-coated might be due to a higher proportion of COO – groups.…”
Section: Resultsmentioning
confidence: 99%
“…The surface charge measured in distilled water was negative for BSA-SeNPs (−34.5 mV), UD-SeNPs (−26.6 mV), and AgNPs (−29.8 mV) and positive for CS-SeNPs (+24.4 mV). Generally, the ions in PBS seemed to neutralize the zeta potential attributable to an increased salt concentration in PBS. , However, even using PBS instead of water to dissolve the NPs, BSA-SeNPs, UD-SeNPs, and AgNPs remained negatively charged, while CS-SeNPs stayed positively charged (Table ). Cao et al (2019) reported that the positive surface charge provided by CS could be mainly attributed to NH 3 + groups, while the net negative charge in BSA-coated might be due to a higher proportion of COO – groups.…”
Section: Resultsmentioning
confidence: 99%
“…The slight reduction in adsorption despite the increase in salinity, with an increase of the nanoparticle concentration from 0.01 to 0.1 w/w to almost 20% reduction, could be explained by the nanoparticles’ repulsive forces diffusing away from the bulk solution to the clay’s surfaces . This is because the ion charge’s efficiency to shield the nanoparticles and cause a reduction in the repulsive forces between the nanoparticles will be reduced with increasing the concentration of the nanoparticle.…”
Section: Resultsmentioning
confidence: 99%
“…Salinity is able to change the aggregation and arrangement of nanoparticles on the surface of oil sand, and even affect the adsorption of the ODA-MoS 2 nanofluid on the surface of oil sand. 39 It is of great significance to study the effect of salinity on the adsorption of the ODA-MoS 2 nanofluid, optimize the appropriate salinity value, and make the equilibrium adsorption capacity reach the minimum for the study of EOR of the ODA-MoS 2 nanofluid. The salinity of Daqing formation water is 6586.15 mg/L, and the change of salinity is the multiples of formation water salinity, respectively.…”
Section: Effect Of Salinity On the Static Adsorption Capacitymentioning
confidence: 99%